2016
DOI: 10.1590/0103-6440201600926
|View full text |Cite
|
Sign up to set email alerts
|

Murine Experimental Root Canal Infection: Cytokine Expression in Response to F. nucleatum and E. faecalis

Abstract: The aim of this study was to evaluate the gene expression of proinflammatory (RANKL, TNF-a and IFN-g) and regulatory (TGF-b and IL-10) cytokines as reaction to experimental infection by mono or bi-association of Fusobacterium nucleatum (ATCC 10953) and Enterococcus faecalis (ATCC 19433). F. nucleatum and E. faecalis, either in mono- or bi-association were inoculated into the root canal system (RCS) of Balb/c mice. Animals were sacrificed at 10 and 20 days after infection and periapical tissues surrounding the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Prostaglandins mediate the alveolar bone absorption by Porphyromonas gingivalis , Campylobacter rectus and Fusobacterium nucleatum [45]. F. nucleatum can act on osteoblasts reflecting in the reduction of osteogenic gene expression and proteins [46], in the inhibition of, cell differentiation, formation of mineralised nodules and increased production of pro‐inflammatory factors [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prostaglandins mediate the alveolar bone absorption by Porphyromonas gingivalis , Campylobacter rectus and Fusobacterium nucleatum [45]. F. nucleatum can act on osteoblasts reflecting in the reduction of osteogenic gene expression and proteins [46], in the inhibition of, cell differentiation, formation of mineralised nodules and increased production of pro‐inflammatory factors [45].…”
Section: Discussionmentioning
confidence: 99%
“…Prostaglandins mediate the alveolar bone absorption by Porphyromonas gingivalis, Campylobacter rectus and Fusobacterium nucleatum [45]. F. nucleatum can act on osteoblasts reflecting in the reduction of osteogenic gene expression and proteins [46],…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenic infection is an important cause of bone loss in diseases such as periodontitis, dental cysts, bacterial arthritis, and osteomyelitis ( Bolstad et al, 1996 ; Almstahl and Wikstrom, 1999 ; Reis et al, 2016 ). Pathogens such as Actinobacillus actinomycetemcomitans and Porphyromonas gingivalis ( P. gingivalis ) can produce a group of molecules that have potential effects on osteoblast cells and participate in bone loss ( Nair et al, 1996 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pathogens such as Actinobacillus actinomycetemcomitans and Porphyromonas gingivalis ( P. gingivalis ) can produce a group of molecules that have potential effects on osteoblast cells and participate in bone loss ( Nair et al, 1996 ). Fusobacterium nucleatum ( F. nucleatum ) has been frequently reported in gingivitis, periodontitis, pulpal necrosis, and dental pulp infection (caused by chronic apical periodontitis) ( Siqueira and Rocas, 2009 ; Reis et al, 2016 ; Kook et al, 2017 ). In periodontitis, the detection rate and quantity of F. nucleatum are positively correlated with gingival inflammation and periodontal tissue damage ( Yang et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between these two bacteria has contributed significantly to the occurrence of endodontic lesions [10]. Reis et al (2016) have conducted in vivo studies on mice, and results showed that exposure to F. nucleatum biofilms and both F. nucleatum and E. faecalis could induce higher expressions of RANKL, TNF-α, and interferon-gamma than exposure to E. faecalis biofilm on the 10 th day [11]. F. nucleatum may be found in oral cavity infections, such as post-treatment endodontic diseases, acute dental abscess, endodontic flare-ups, and periodontal disease [4,9].…”
Section: Introductionmentioning
confidence: 99%